A Vector Control Strategy to Eliminate Active Power Oscillations in Four-Leg Grid-Connected Converters Under Unbalanced Voltages - Diaz-Diaz, M (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
The problems associated with active power oscillations (APOs) in grid-connected converters are well-known. Imbalances in the grid usually produce double-frequency oscillations in the dc-link voltage and current which could reduce the useful life of solar panels, batteries, and capacitors connected to this point. Moreover, as reported in the literature, double-frequency reactive power oscillations (RPOs) also produce adverse effects in distribution systems, and it is desirable to eliminate or mitigate them. When a four-leg power converter is connected to an unbalanced grid, the zero-sequence current provides extra degrees of freedom to compensate or even eliminate the power oscillations at the converter dc-link side. In this paper, a new methodology to regulate these double-frequency power components is proposed. It is based on a closed-loop vector control approach, where the active power oscillations (APOs) at converter side are transformed into a synchronous frame rotating at twice the grid frequency and regulated using the zero-sequence current. To avoid overcurrent produced by the circulation of positive-, negative-, and zero-sequence components a current limiter is also proposed in this paper. Experimental results obtained with a 4-kW four-leg power converter prototype are presented and discussed in this paper.